Incantation in sogit ritual: a preliminary study - Syamsul Azizul Marinsah; Suraya Sintang; Abdul Hair Beddu Asis; Abang Mohd. Razif Abang Muis; Mohd Anuar Ramli (PalArch Foundation, 2020)
Incantation can be described as a two-way mediator between human and supernatural beings that reflects the expression of compliant, submission, and obedience. Mantras are sacred and can only be recited by traditional practitioners. Recitations of mantras must be in accordance with the sogit ritual. Hence, the objective of the study is to identify types of mantras that are recited in sogit rituals among the Bobolians (female traditional practitioner) in Sabah. This qualitative study uses data document analysis for data sampling method. The findings stated that the content of mantras in the sogit ritual portrays community invocation specifically the Bobolians towards supernatural beings.They are believed to possess supernatural powers and regarded as the guardians of the world that is produced by nature. Mantras are used as medium of interaction to communicate with supernatural beings from supernatural realm.